2019
DOI: 10.1155/2019/6252013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Xylanase Pretreatment on the Quality of Refiner Mechanical Mulberry Branch Fibers

Abstract: We performed xylanase pretreatment prior to mechanical refining in the production of mulberry branch fibers, with the objective of saving energy and studying the effects of such pretreatment on the quality of the fibers. To determine the effects of the enzyme action, we analyzed the energy required for refining, related yield, and the dimension, deformation, and morphology of the fibers. We found that, with the xylanase pretreatment, the refining energy was reduced by 4%, with the yield of fibers being maintai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Different amounts of hemicelluloses may also be responsible for the differences in the performance of EnzB as this enzyme formulation also exhibited a high xylanase activity, while filter paper only exhibits low amounts of hemicelluloses. Several studies have reported that xylanases contribute positively to refining of pulps in terms of energy reduction (Tao et al 2019). Despite the successful demonstration of the effectiveness of energy reduction by xylanases, their use can also affect the paper properties like tensile strength negatively by the removal of xylan (Miletzky et al 2015;K.…”
Section: Comparison Of Refining Enzyme Formulationsmentioning
confidence: 99%
“…Different amounts of hemicelluloses may also be responsible for the differences in the performance of EnzB as this enzyme formulation also exhibited a high xylanase activity, while filter paper only exhibits low amounts of hemicelluloses. Several studies have reported that xylanases contribute positively to refining of pulps in terms of energy reduction (Tao et al 2019). Despite the successful demonstration of the effectiveness of energy reduction by xylanases, their use can also affect the paper properties like tensile strength negatively by the removal of xylan (Miletzky et al 2015;K.…”
Section: Comparison Of Refining Enzyme Formulationsmentioning
confidence: 99%
“…Microorganism-derived xylanases might be useful in the feed, food, wastepaper, and various agricultural sectors [11,12]. Xylanase has been shown to save energy and improve yield and pulp properties in biomechanical pulping processes, through pre-treatment of pulps before bleaching in the pulp and paper industry [13,14]. Recently, ink from effluent generated from paper and pulp industries can be remove by using xylanase and laccase enzymes [15].…”
Section: Introductionmentioning
confidence: 99%
“…Further, the fiber widths increased because of the improved swelling effect of the xylanase pretreatment. In some instances, the fine elements were reduced (Tao et al 2019). Poplar wood is a fast-growing hardwood species.…”
Section: Introductionmentioning
confidence: 99%